The apostle and the empire : Paul's implicit and explicit criticism of Rome - Heilig, Christoph (1990-) (William B. Eerdmans Publishing Company, 2022)
"A study of Paul's engagement with the Roman Empire in his New Testament letters, in which Christoph Heilig argues that Paul hid criticism of Rome in the subtext of his letters but also openly denounced it in passages that scholars have previously overlooked"-- Provided by publisher. "Was Paul silent on the injustices of the Roman Empire? Or have his letters just been misread? The existence of anti-imperial rhetoric in the writing of the apostle Paul has come under greater scrutiny in recent years. Pressing questions about just how much Paul actually addressed Rome in his letters and how publicly critical he could have afforded to be have led to high-profile debates-most notably between N. T. Wright and John M. G. Barclay. After having entered the conversation in 2015 with his book Hidden Criticism?, Christoph Heilig contributes further insight and new research in The Apostle and the Empire to argue that the case for Paul hiding his criticism of Rome in the subtext of his letters has more merit than previously claimed by scholars like Barclay. Moreover, he argues that there are also passages that contain more open denouncements of the Roman Empire that scholars have previously overlooked-for instance, in the mention of a "triumphal procession" in 2 Corinthians, which Heilig discusses in great detail by drawing on a variety of archaeological data. Heilig's groundbreaking work constitutes a must-read for Pauline scholars but also for anyone interested in the intersection of Christianity and empire and how one of the Christian tradition's most important teachers communicated his unease with the global superpower of his day. Furthermore, Heilig takes on larger issues of theory and methodology in biblical studies, raising significant questions about how interpreters can move beyond outdated methods of reading the New Testament toward more robust understandings of the ways ancient texts convey meaning"